More Than Just "Blowing off Steam": The Roles of Anger and Advocacy in Promoting Positive Outcomes at Work. (May 2016) - Stickney, Lisa T.; Geddes, Deanna
Abstract: Employee anger can be suppressed or quieted so that angry individuals only vent frustrations to supportive colleagues, rather than approach those responsible or in an organizational position to help remedy the problematic situation. The Dual Threshold Model (Geddes & Callister, 2007 ) argues that although these "muted anger" venting episodes may increase unfavorable organizational outcomes, they also may prompt participants or observers of these displays to engage in advocacy or surrogacy on behalf of an angry colleague. The research reported here empirically tests this proposition and reports that advocating on behalf of one's angry colleague can enhance individual relationships at work as well as organizational functioning. Findings also show that observer felt anger intensity is a primary motivator for prompting anger advocacy and, surprisingly, advocacy is less likely on behalf of close colleagues.